Gamification in Programming - a Short Introductory Session in Programming with Online Games - Ádámkó, Éva (International Journal of Engineering and Management Sciences, 2018)
Nowadays computer science is a diversified discipline with a wide range of interdisciplinary applications. Because of that, teachers at primary or high schools unavoidably face the following problem: What are the most useful fields, topics and applications of computer science and programming, and how can we teach them to be motivating enough for a student from the Z generation. In this paper we give a possible answer for the question above by presenting a short introductory session in programming for students in primary and high school. Our primary aim with the above session is to motivate students to continue their studies in engineering higher education. We also present our experiences about two experimental classes here.